Active methodologies for mathematics teaching in the early years: learning through games - Camara Lubachewski, Gesseca; Cerutti, Elisabete (Faculdade de Educação/Universidade Estadual de Campinas, 2020)
This article is a bibliographical study about Active Methodologies for Mathematics through Games in the early years of Teaching School, focused on teaching situations that can stimulate and instigate students. The purpose of this study is to present reflections on differentiated methodologies in Mathematics teaching in the initial years and the development of skills and abilities needed to understand reality, making decisions based on the most diverse situations of daily life, teacher-student interaction and contributions for more meaningful learning. The theoretical framework provides approaches on Active Methodologies in the teaching of Mathematics and Learning through Games. Among the partial results are possible benefits and methodological possibilities for the teaching-learning process of Mathematics, as well as actions that contemplate the use of diversified strategies, between them, learning through games.